Buddhist cosmology science and theology in the images of motion and light - Kloetzli W Randolph (Delhi Motilal Banarsidass, 1989)
This work attempts to begin the process of interpreting the major phases of Buddhist Cosmological speculation by seeing in them various dramas of salvation tailored to the philosophical and theological predilections of their respective traditions. To a l
Keywords: Buddhist cosmology